(3GbJUGOjGJ GdONd Gdbhej hGdeGdjI GdYGeIs - (3GdLfGHj(B, (3gjKe YHO GdbGOQs; (3aGFR, TGcQ CMeOs ((3YeGfs (3EHUGQ fGTQhf hehRYhf s, 2022)
(3jgJe cJGH (B"(3GbJUGOjGJ GdONd Gdbhej hGdeGdjI GdYGeI(B" (3HOQS LhGfH CSGSjI ef GdGbJUGO Gdcdj(B. (3jHOC GdcJGH HJYQja eaGgje GdONd Gdbhej hGdfGJL Gdbhej, Ke jfJbd Edi OQGSI echfGJ GdWdH Gdcdj eKd GdGSJgdGc hGdGSJKeGQ(B. (3jJfGhd GdcJGH HYO Pdc OhQ GdfbhO hGdHfhc aj GdGbJUGO, hcjajI GSJNOGe GdSjGSI GdfbOjI decGaMI GdJVNe(B. (3jfJbd GdeDdaGf HYO Pdc Edi OQGSI GdeGdjI GdYGeI, eJfGhdjf WHjYJgG hCgejJgG, Ke jSJYQVGf HGdJaUjd GdfabGJ GdYGeI hGdEjQGOGJ GdYGeI, eY GdJQcjR HTcd NGU Ydi GdVQGFH hGdbQhV GdYGeI(B. (3hjNJJe GdcJGH HOQS GdehGRfI GdYGeI hOhQgG aj EOGQI GdGbJUGO(B.s
Keywords: (3GdSjGSI GdeGdjI (B- (3GdGjQGOGJs; (3GdeGdjI GdYGeI (B- (3GdONd Gdbhejs